The Post 1992 Biodiversity Legal Protection Systems in Brazil and Colombia:: Considerations and Perspectives - Bachega, Luciana Ruggiero; Espíndola, Isabela Battistello; Neves, Luiza de Lima; Moschini, Luiz Eduardo (Sustainability in Debate, 2017)
The article analyses how Brazilian and Colombian legal systems deal with the protection of their biodiversity, especially after both joined the Convention on Biological Diversity (CBD) during the RIO-92 Conference. Being one of the fundamental properties of nature, biodiversity is of interest of national states, not only for the use of their natural assets, but also for protection and conservation purposes. In this study, a survey of the principles and guidelines of the CBD was carried out. The internal regulations of each country were also taken into consideration. We conclude that, in spite of their previous environmental regulations, dating from before 1992, both countries fostered the evolution of their regiments on biodiversity after the CBD. However, and as it happens with other international agreements, the Convention’s Commandments still find it difficult to be effectively applied. Scientific evidence shows that local fauna, flora and the environment as a whole are still in need of legal protection. The effective implementtion of actions for the conservation of biological diversity is still unclear.